2021
DOI: 10.1109/access.2021.3112849
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Ureido and Methacrylate Functionalities Onto Silica Nanoparticles and its Effect on the Properties of Polypropylene-Based Nanodielectrics

Abstract: Surface modification of nanoparticles is often utilized to tailor the interfacial properties in dielectric nanocomposites. Introducing different functional groups to the nanoparticles' surface may induce localized states (traps) that can enhance the dielectric performance of the material depending on their density and energy levels. Furthermore, surface modification of the filler can affect the dispersion quality and crystallization of the nanocomposites which can ultimately alter the dielectric response of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Deep traps, with energies above 1 eV, can effectively immobilize charge carriers, reduce the hopping conduction of electrons, and cause the formation of homocharge near the electrodes . For instance, it has been shown that functionalization of NPs with polar moieties can induce trapping states at the filler-polymer interfaces, reduce the charge carrier mobility and accumulation under electric fields, and ultimately enhance the dielectric properties of the corresponding NCs. Therefore, engineering the density and depth of traps in the material is crucial for designing high-performance insulating nanodielectrics. This can be realized by grafting functional groups with different electronic structures onto the NPs, introducing new localized states with different energy levels compared to the bare NP.…”
Section: Introductionmentioning
confidence: 99%
“…Deep traps, with energies above 1 eV, can effectively immobilize charge carriers, reduce the hopping conduction of electrons, and cause the formation of homocharge near the electrodes . For instance, it has been shown that functionalization of NPs with polar moieties can induce trapping states at the filler-polymer interfaces, reduce the charge carrier mobility and accumulation under electric fields, and ultimately enhance the dielectric properties of the corresponding NCs. Therefore, engineering the density and depth of traps in the material is crucial for designing high-performance insulating nanodielectrics. This can be realized by grafting functional groups with different electronic structures onto the NPs, introducing new localized states with different energy levels compared to the bare NP.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the breakdown strength of the epoxy composites with inorganic fillers increases due to the suppressed space charge accumulation [22][23][24]. In nanocomposites, it is noted that the traps generated at the filler-polymer interface and a higher charge injection barrier was present [25][26][27]. Studies on the interaction mechanism of interface have a very important impact on the explanation of properties of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the practical use of such inorganic NPs is still limited because of their high surface energy and chemically different surface characteristics that increases their tendency to agglomerate making nely dispersing them within the polymeric matrix di cult [15,16]. Therefore, considerable research has been devoted to homogeneously disperse NPs within the polymeric matrix through surface functionalization of the NPs, including covalent or non-covalent functionalization [17][18][19].…”
Section: Introductionmentioning
confidence: 99%